A Comprehensive Analysis Of Bhallatakadi Churna In The Management Of Amavata w.s.r To Rheumatoid Arthritis - Parihar, Rahul; Dadhich, Suman; Pandey, A K (International Research Journal of Ayurveda & Yoga, 2021)
The Amavata of Ayurveda can be correlated with Rheumatoid Arthritis of contemporary medical science. Rheumatoid Arthritis is a chronic inflammatory systemic disorder triggered by auto-immunity to self-antigens. Its available modern management is still not satisfactory. Hence, majority of the patients are inclined towards the traditional systems of medicine including Ayurveda. Bhallatakadi Churna (comprises of 3 herbal drugs i.e., Bhallataka (Semecarpus anacardium Linn.), Tila (Sesamum indicum Linn.) & Haritaki (Terminalia chebula Retz.) is one of the promising herbal formulations, mentioned in Yogaratnakara for the management of Amavata (Rheumatoid Arthritis). It has capacity to alter basic matrix (Ama, Vata, Agnimandya) of diathesis of Amavata (Rheumatoid Arthritis). These drugs impart Deepana (appetizer), Rasayana (Rejuvenator), Anulomana (carminatives), Pachana (Digestive), Ama-doshahara, Medhya Prabhva (Nootropic) & Shothahara (anti-inflammatory) effect. So, this formulation used in Amavata (Rheumatoid Arthritis) not only pacify and correct the Ama & Vatadosha, but it also hit on the root cause of disease i.e., Mandagni (weak digestive fire). The critical evaluation of pharmacological actions of these drugs reveals its anti-oxidant, anti inflammatory, anti-nociceptive etc. effects, which is quite enough to modify the root cause of disease i.e., auto antigen (most correlative with Ama) and pacify the chief complaint of the patients of Rheumatoid Arthritis. In this article we will try put an emphasis on Bhallatakadi Churna by incorporating the classical and contemporary knowledge.